MODELING INPUT DATA CLASSES OF THE BUILDING ENERGY SIMULATION PROGRAM ENERGY PLUS WITH SCENARIOS AND HIERARCHICAL COLORED PETRINETS (Sciences & Technologie. B, Sciences de l'ingénieur, 2014)
This paper addresses the problem of modeling input data classes of the input data dictionary (IDD) file of the Building energy simulation program EnergyPlus. Our endeavor is to provide an easy way for elaborating a behavior specifications of an interactive user interface intended for input data of the IDD file, using hierarchical colored Petri nets.The modeling approach used in this work comprises two levels of abstraction: the use case level corresponding to the use case diagram model as defined in the unified modeling language (UML) and the scenario level as refinement of the former one.  The color aspect of Petri-nets is used at the scenario level to preserve the independence of several scenarios after their integration. The benefit of the approach consists in the structuring of the scenario acquisition and the approach of merging scenarios using composite color sets.